Controlled construction of 3D self-assembled VS4 nanoarchitectures as high-performance anodes for sodium-ion batteries. (1st June 2018) - Li, Wenbin; Huang, Jianfeng; Cao, Liyun; Feng, Liangliang; Yao, Chunyan
Abstract: Developing desirable anode materials with 3D self-assembled structure is of paramount importance for enhancing the performance of sodium-ion batteries. Here, we report the controlled synthesis of three novel 3D VS4 nanoarchitectures: nanorods (Nanorod-VS4 ), nanocones and nanobelts self-assembled VS4 microspheres. When serving as anode materials for sodium-ion batteries, Nanorod-VS4 exhibits the better electrochemical performances than the latter two, delivering a high reversible capacity of 225 mAhg −1 at 0.5 Ag -1 after 200 cycles and that of 203 and 168 mAhg −1 even at 1.0 and 2.0 Ag -1, respectively. The remarkable sodium storage properties of the Nanorod-VS4 material is mainly ascribed to the synergistic effect of the self-assembled structure of radial nanorods and the preferred orientation growth along (110) planes. Moreover, the reversible insertion reaction and diffusion-dominant Na + storage process between 0.50 and 3.00 V occurring in the Nanorod-VS4 are clearly revealed. Graphical abstract: Image 1